Kolej Risda Plants seeds Of Success - New Straits Times, (2008)
With agriculture identified as an engine of growth under the Ninth Malaysia Plan, the government is striving to modernise the sector through large scale commercial schemes use of technology,high-quality commodities and more value-added products